Reflection from the prophetic guidance on plague - Mohd Marzuki, Zunaidah (The IIUM Covid19 Psychosocial Support Team, 2020)
Undeniably, the current Covid19 plague is one of the hardest tribulations that disrupted the life of many – be it physically, mentally, spiritually, economically, etc. It has changed many aspects of our life and abruptly made us undergo many new norms and phenomena, including the quarantine. It has taught us how to overcome the unexpected hardships with the right mindset and suitable adaptation.